Обобщенная методика минимизации массы электромеханического аккумулятора (ЭМА) - Подгорнов, А.; Сипович, А. (Технічна електродинаміка, 2012)
In this paper electromechanical battery mass minimization method is described; battery includes an electromechanical transducer and a steel flywheel. Using the synchronous electrical machines with electromagnetic excitation design equations and the flywheel strength equation, EMA mass functions is created for application which works in generator mode. For battery mass function minimization a special computer program was written in TURBO PASCAL language. As a numerical example of the minimum mass calculation, battery for electric transport network is presented.